2018
DOI: 10.1038/s41564-018-0203-x
|View full text |Cite
|
Sign up to set email alerts
|

A gated relaxation oscillator mediated by FrzX controls morphogenetic movements in Myxococcus xanthus

Abstract: Dynamic control of cell polarity is of critical importance for many aspects of cellular development and motility. In Myxococcus xanthus, MglA, a G protein, and MglB, its cognate GTPase-activating protein, establish a polarity axis that defines the direction of movement of the cell and that can be rapidly inverted by the Frz chemosensory system. Although vital for collective cell behaviours, how Frz triggers this switch has remained unknown. Here, we use genetics, imaging and mathematical modelling to show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
137
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(154 citation statements)
references
References 39 publications
11
137
1
Order By: Relevance
“…20 Recent studies based on cell tracking have provided unprecedented detail of cell 21 movement during development [7]. In combination with mathematical modeling, these 22 datasets unambiguously identified individual cell behaviors that are essential for 23 42 help of A-motility system that uses a novel molecular motor and focal adhesion 43 complexes [9,21]. However, most S-system mutants fail to develop because they cannot 44 produce an extracellular matrix (ECM) that is both essential for S-motility and vital for 45 development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Recent studies based on cell tracking have provided unprecedented detail of cell 21 movement during development [7]. In combination with mathematical modeling, these 22 datasets unambiguously identified individual cell behaviors that are essential for 23 42 help of A-motility system that uses a novel molecular motor and focal adhesion 43 complexes [9,21]. However, most S-system mutants fail to develop because they cannot 44 produce an extracellular matrix (ECM) that is both essential for S-motility and vital for 45 development.…”
mentioning
confidence: 99%
“…It is frequently difficult to ascertain which of 8 the behavioral changes are deleterious to development and which can be tolerated. Here 9 we develop a new approach that leverages data-driven modeling to determine whether a 10 statistically significant trend in cell behavior results in biologically significant alteration 11 of the multicellular program. We demonstrate this approach by focusing on full or aggregation [7,34].…”
mentioning
confidence: 99%
“…Such patterns can be manifested in both space and time, with perhaps the most widespread instance of the latter being provided by systems that exhibit relaxation oscillations (see, e.g., Refs. [3][4][5][6]). In the simplest scenarios, these can be understood as resulting from interactions between an activator component and an inhibitory (or inactivation) component that operate at fast and slow time-scales respectively [7].…”
mentioning
confidence: 99%
“…1A), while it rapidly diffuses in the cytoplasm. This simplest scenario is a good approximation for the M. xanthus polarity system [21] and suffices to reveal general principles of signal-induced polarity switching, as we will see below. The distribution of A is then characterized by quantifying its abundance at pole '1' and '2', as well as in the cytoplasm, and the timedependent cell polarity can be defined as…”
Section: Resultsmentioning
confidence: 97%
“…Recently, Guzzo et al [21] identified the response regulator FrzX as a mediator of the Frz reversal signal to the Mgl system, and proposed a mechanism for how FrzX can interact with the three core polarity proteins to trigger polarity reversals. Here, we take this study as a starting point to explore the question of signal-induced polarity switching on a more general level.…”
mentioning
confidence: 99%